Visitor’s risk awareness towards water recreation activities at Tasik Dayang Bunting, Langkawi, Kedah - Zulkifly, Muhammad Hafizul Hilmi (2019)
Over the years tourism has grown rapidly and for many regions and countries worldwide, it is an important sector. It is also said that tourism is the largest sector in the world and many people participate in this sector. Recreation becomes an alternative choice to release stress from work, studies and any of problem occurred. The accident during water recreation activities always happen at anywhere and anytime. This is due lack of information related with the safety and risk awareness about water recreation activity can therefore lead to the accident at the recreation place that can affects perception of visitor’s towards safety and the profit will reduced. This assessment needed to know the visitor’s risk awareness towards water recreation activities at Tasik Dayang Bunting Langkawi, Kedah. The 150 questionnaires were distributed towards visitor’s to know level of safety knowledge on water recreation activities. In addition, on the result shown the shows the positive effect of respondents about the level of visitors risk awareness towards water recreational activities. The evaluations of visitor’s motive to do water recreational activities in TDB are to encourage visitors to view and enjoy the environment of the existing recreational areas in Malaysia including in TDB. Then, the socio-demographic of visitors are from multiple races and from overseas who come to TDB. This analysis really important because important to prevent any circumstances and can reduced the risk’s death due of drowning.